Lipocalin-2 in Fructose-Induced Fatty Liver Disease - Lambertz, Jessica; Berger, Thorsten; Mak, Tak W.; van Helden, Josef; Weiskirchen, Ralf (Frontiers in Physiology, 2017)
The intake of excess dietary fructose most often leads to non-alcoholic fatty liver disease (NAFLD). Fructose is metabolized mainly in the liver and its chronic consumption results in lipogenic gene expression in this organ. However, precisely how fructose is involved in NAFLD progression is still not fully understood, limiting therapy. Lipocalin-2 (LCN2) is a small secreted transport protein that binds to fatty acids, phospholipids, steroids, retinol, and pheromones. LCN2 regulates lipid and energy metabolism in obesity and is upregulated in response to insulin. We previously discovered that LCN2 has a hepatoprotective effect during hepatic insult, and that its upregulation is a marker of liver damage and inflammation. To investigate if LCN2 has impact on the metabolism of fructose and thereby arising liver damage, we fed wild type and Lcn2-/- mice for 4 or 8 weeks on diets that were enriched in fructose either by adding this sugar to the drinking water (30% w/v), or by feeding a chow containing 60% (w/w) fructose. Body weight and daily intake of food and water of these mice was then measured. Fat content in liver sections was visualized using Oil Red O stain, and expression levels of genes involved in fat and sugar metabolism were measured by qRT-PCR and Western blot analysis. We found that fructose-induced steatosis and liver damage was more prominent in female than in male mice, but that the most severe hepatic damage occurred in female mice lacking LCN2. Unexpectedly, consumption of elevated fructose did not induce de novo lipogenesis or fat accumulation. We conclude that LCN2 acts in a lipid-independent manner to protect the liver against fructose-induced damage.